Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Smartphone Merek Oppo - Setiono, Beni Agus; Sustiyatik, Enni (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
The purpose of this study was to test and analyze the factors that influence the purchasing decision for the OPPO brand smartphone. This type of research is an associative study which explains the relationship and influence between the variables of product quality, price, and promotion on purchasing decisions. The population in this study were students in the city of Kediri who had bought and used the OPPO brand smartphone. The sampling technique used purposive sampling. With a sample size of 60 respondents. Data analysis using SEM (Structural Equation Model) method. Based on the results of research and data analysis, it is concluded that the variable product quality does not have a significant effect on purchasing decisions, while the price and promotion variables have a significant effect on purchasing decisions.